Supplementing insect meal and fish protein hydrolysates in barramundi, Lates calcarifer diet improves the inclusion efficiency of poultry by-product meal: a physiological approach - Chaklader, Md Reaz (Curtin University, 2021)
The research investigated the complete replacement of fishmeal (FM) with a mixture of multiple protein ingredients including poultry by-product meal (PBM), black soldier fly, Hermetia illucens (HI) larvae meal, and fish protein hydrolysates (FPHs) originating from recycled food wastes. The results showed that supplementation of HI and FPH separately or concurrently with PBM can replace FM completely from the juvenile barramundi diet with an improvement in physiological and immunological responses and final product quality.